COPING PATTERNS OF WOMEN BREAST CANCER SURVIVORS IN KIGALI-RWANDA A PHENOMENOLOGICAL STUDY - ASEMOTA, Olukemi Olufunmilola; Rwanda, Kigali (IJRDO - Journal of Business Management, 2015)
Breast cancer is one of the leading causes of cancer deaths amongst women worldwide. Mostwomen diagnosed with breast cancer live throughout life with some challenges and thereby adoptsome coping mechanisms in order to minimise their ordeal. This study examined the copingpatterns exhibited by Women Breast Cancer Survivors (WBCS). A phenomenological researchdesign was employed with the snow ball approach for data collection. Ten (10) WBCS wereinterviewed with average age of 40 years. The results show that WBCS shared common fourcoping patterns, namely: spirituality, support from family and friends, the medical team, the useof prosthesis. Other emerged sub themes were: disease removal not organ removal, and socialisingwith other victims of breast cancer. The results showed that women who survived breast canceralways have a story to tell on their coping patterns despite the debilitating physical and emotionaltraumas of living with breast cancer.